Efektivitas Penggunaan E-LKPD Materi Reaksi Redoks Berbasis Problem Based Learning terhadap Hasil Belajar Peserta Didik Fase E SMTI Padang - Sampaikan Sabda Zebua; Syamsi Aini (MASALIQ, 2026)
Although the integration of digital learning media has received attention in various previous studies, research that specifically discusses the effectiveness of Problem-Based Learning (PBL)-based E-LKPD in improving learning outcomes on redox reaction material remains limited. This study aims to evaluate the effectiveness of using PBL-based E-LKPD on redox reaction material on the learning outcomes of Phase E students at SMK SMTI Padang. This study used a quantitative approach with a pre-experimental design in the form of a one-group pretest-posttest design, involving 35 students selected using purposive sampling. Data were collected using a multiple-choice test instrument administered in the form of a pretest and posttest, then analyzed using the N-Gain test. The results showed a significant improvement in learning outcomes, with the average score increasing from 29.64 in the pretest to 88.39 in the posttest, and an N-Gain score of 0.83 in the high category. These findings contribute to the development of constructivism-based learning and expand understanding of the integration of digital media with problem-based learning. The conclusion of this study confirms that PBL-based E-LKPD is effective in improving students’ conceptual understanding and learning outcomes on redox reaction material. The implications of this study include theoretical contributions to digital learning innovation and practical implications for educators in improving the quality of chemistry learning through the use of PBL-based E-LKPD.